PENDAMPINGAN PENGEMBANGAN PELAKU UMKM NASABAH BANK BTPN SYARIAH OLEH FASILITATOR PENDAMPING DI MMS MAOS - Taufiequrahman, Gus; Pamikatsih, Mutia (LPPM Universitas Flores, 2024)
The role of mentoring facilitators in developing SMEs for BTPN Syariah bank customers in MMS MAOS. MMS (Sharia Mobile Marketing) is a BTPN Syariah Bank branch office, which is placed in villages. MMS Maos is in the Maos sub-district, Cilacap district. This MMS covers 2 sub-districts, namely the Maos sub-district and the Adipala sub-district. In this MMS many customers are mothers who have MSME businesses. most of the run companies are still quite simple. For this reason, BTPN Syariah Bank collaborates with students to assist female customers of BTPN Syariah Bank to provide business assistance for customers, so that customers' businesses can develop further. The method for implementing this activity is by conducting coaching and socialization according to the material obtained from the customer assessment analysis and the customer will carry out a SWOT analysis to find out the obstacles experienced by the customer. Then the customer will be accompanied through material and practice. The aim of this activity is that customers are able to understand and directly implement the results obtained during mentoring, so that there is development of the customer's business.